A Portrait of English Secondary Teachers in Indonesia in Exploiting Questions Referring to Bloom’s Taxonomy - Dahnilsyah, Dahnilsyah (Journal of Educational Sciences, 2020)
This study sheds light on the skill of three secondary school English teachers in Indonesia in making use of questions referring to the Bloom’s Taxonomy to keep students engaged in the course of the lesson. It adopts qualitative content analysis where the stages of decontextualization, recontextualization, categorization, and compilation were conducted. Three YouTube videos which provide the teaching performance of these three teachers had been the data collected in this study. From the findings, it discovers that these three English teachers still preferred applying the lower-order thinking questions to higher-order thinking questions which had been the type of teachers in Asia, including Indonesia. Consequently, students did not get ample chance to develop their critical thinking skills. This study therefore highly recommends that teachers need to get much exposure to the higher-order thinking questions as it is one of the demanding skills needed in the 21 first century.